2020
DOI: 10.3390/en13164048
|View full text |Cite
|
Sign up to set email alerts
|

Management Challenges and Opportunities for Energy Cloud Development and Diffusion

Abstract: The use of emerging technologies such as cloud computing, Internet of Things, and Big Data, is increasing as tools to assist the management of data and information related to energy systems grow. This allows for greater flexibility, scalability of solutions, optimization of energy use, and management of energy devices. In this sense, the objective of this research is to present the basic elements and requirements for the energy cloud and its management and discuss the main management challenges and opportuniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 124 publications
(283 reference statements)
0
28
0
Order By: Relevance
“…In this sense, the EC allows the dynamic integration of different technologies in an intelligent network environment 25 . The EC scenario relies on cloud computing.…”
Section: Energy Cloudmentioning
confidence: 99%
See 3 more Smart Citations
“…In this sense, the EC allows the dynamic integration of different technologies in an intelligent network environment 25 . The EC scenario relies on cloud computing.…”
Section: Energy Cloudmentioning
confidence: 99%
“…As it is a recent topic, the research area focused on EC is still being developed. The basic elements and requirements for the EC and its management were studied, 25 as well as the migration of Industrial Energy Management Systems to the cloud 23 . The authors also concluded that the application of these technologies can generate new opportunities for saving energy and costs.…”
Section: Energy Cloudmentioning
confidence: 99%
See 2 more Smart Citations
“…Sustainable energy generation holds great promise for resolving current energy and environmental challenges (Hu et al, 2017) together with strategies for managing limited energy resources (Schaefer et al, 2020). The main goal of increasing the spread and use of renewable energy generation systems is to reduce the use of fossil fuels and greenhouse gas emissions (Roselli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%